Anticipatory Traumatic Reaction: Outcomes Arising From Secondary Exposure to Disasters and Large-Scale Threats. (December 2019) - Hopwood, Tanya L.; Schutte, Nicola S.; Loi, Natasha M.
Two studies, with a total of 707 participants, developed and examined the reliability and validity of a measure for anticipatory traumatic reaction (ATR), a novel construct describing a form of distress that may occur in response to threat-related media reports and discussions. Exploratory and confirmatory factor analysis resulted in a scale comprising three subscales: feelings related to future threat; preparatory thoughts and actions; and disruption to daily activities. Internal consistency was .93 for the overall ATR scale. The ATR scale demonstrated convergent validity through associations with negative affect, depression, anxiety, stress, neuroticism, and repetitive negative thinking. The scale showed discriminant validity in relationships to Big Five characteristics. The ATR scale had some overlap with a measure of posttraumatic stress disorder, but also showed substantial separate variance. This research provides preliminary evidence for the novel construct of ATR as well as a measure of the construct. The ATR scale will allow researchers to further investigate anticipatory traumatic reaction in the fields of trauma, clinical practice, and social psychology.